Detection of Avian Leucosis Virus Subgroup J in Poultry Tissue Samples and Their Molecular Characterization - Thapa Chhetri, Bala Ram (2004)
This study was carried out to diagnose and characterize avian leucosis virus subgroup J (ALV-J) specific sequence isolated from poultry organs with myelocytic infiltration. Archived tissues with and without myelocytic infiltration were examined by PCR followed by sequencing. Four ALV-J sequences identified and named as; UPMIA6, UPMIAIO, UPMlA17 and UPMIA18 were characterized based on sequence and phylogenetic analysis. Different diagnostic tests (PCR, ELlSA and Virus isolation) for ALV-J were also studied and compared. A total of 21 poultry tissue samples were examined by PCR using primers (H5lH7) and 16 samples were found positive for ALVJ proviral DNA. However, only 5 samples were found positive for ALV-J viral RNA. Sequence analysis indicated that the 4 sequences have significant homology ( >go%) when compared to A LV-J from U K a nd U SA. However, based on phylogenetic analysis, the sequences of the ALV-J were close to Houghton Poultry Research Station -103 (HPRS-103). In addition 3, 10, 3 and 8 amino acid substitutions were observed in sequences; UPMIAG, UPMIAI 0, UPMIAI 7 and UPMIAI 8, respectively. All these substitutions were unique and have not been reported before from other ALV-J isolates. The importance of these substitutions requires further study especially in order to determine whether the sequences resemble variant ALV-J from UK or USA. Different diagnostic techniques were also compared for the detection of ALVJ in a normal broiler breeder flock as the first isolation of ALV-J was made from normal meat-type chickens. PCR was found to be more sensitive than ELSA and virus isolation. However, even though the chickens were gp85 antibody positive, all the samples examined showed negative result for ALVJ proviral DNA and virus isolation. In addition, no virus was isolated from archived tissue samples with myelocytic infiltration. The actual explanation for this finding is not clear, but several probable factors were presented and discussed. In conclusion, ALV-J proviral DNA were detected in tissue samples obtained from chickens with and without myelocytic infiltration. However, no virus was isolated. The importance of PCR in detecting proviral DNA and viral RNA from chickens with gp85 antibody requires careful examination due to the complex nature of ALV-J infection.